Penerapan Model Pembelajaran Kooperatif tipe time token untuk meningkatkan keaktifan belajar siswa (Program Studi Pendidikan IPS, 2021)
learning in social studies learning, this is seen in the initial observations in the learning process. And this research is also motivated by students' inactivity in learning that has not been trained by the teacher. This study aims to improve student learning activeness in integrated social studies class VIIB SMPN 12 North Tambusai. This type of research is classroom action research with research subjects are students of class VII B SMP N 12 Tambusai Utara. The study was conducted in two cycles, each cycle taken with 2 actions and consisted of 4 stages, namely planning, implementation, observation, and reflection. The research data were obtained from observations during the social studies learning activities taking place using student and teacher observation sheets. Documentation. The results showed that (1) the activeness of student learning in the implementation of learning starting from cycle I and cycle II increased. (2) Evidence of increased student activity, the average activity of cycle I was 56%. In the second cycle, it increased to 77.06%. Thus the Time Token learning method can be used to improve the activity and learning outcomes of Social Studies.